2009
DOI: 10.4028/www.scientific.net/msf.628-629.569
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Joint Strength of SiCp/ Al Metal Matrix Composite by Magnetron Sputtering Method

Abstract: Transient liquid-phase (TLP) bonding of aluminium-based metal matrix composite (MMC) has been investigated. An attempt was made of using an Ag/Cu /Ag film as an interlayer for bonding to improve the joint strength. The oxide on the surface of SiCp/Al MMC was etched completely by plasma. Ag/Cu/Ag film of 8µm thickness was prepared by magnetron sputtering method on the clean bonding surface in the same vacuum chamber. Compared with the same thickness of single Cu foil and Ni foil interlayer, which are widely use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, SiCp/Al composites have poor machinability and are difficult to use in manufacturing large or complex components [8]. Assembling modular SiCp/Al composite parts by welding can break through the limitations of component size and structure, thus significantly broadening their application and achieving huge economic benefits [9,10]. However, due to the huge difference in physical and chemical properties between the SiC particle and the Al matrix, the welding of SiCp/Al composites is difficult [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, SiCp/Al composites have poor machinability and are difficult to use in manufacturing large or complex components [8]. Assembling modular SiCp/Al composite parts by welding can break through the limitations of component size and structure, thus significantly broadening their application and achieving huge economic benefits [9,10]. However, due to the huge difference in physical and chemical properties between the SiC particle and the Al matrix, the welding of SiCp/Al composites is difficult [11].…”
Section: Introductionmentioning
confidence: 99%
“…Particle-reinforced aluminum matrix composites, such as SiCp/Al composites [1], Si 3 N 4 /Al composites [2], SiO 2 /Al composites [3], Al 2 O 3 /Al composites [4], B 4 C/Al composites [5], and TiC/Al composites [6], process excellent electrical and chemical properties, as well as the comprehensive mechanical performances, and have been important structural materials in aerospace, electronics, and automobile industries. Among them, the SiCp/Al composites are particularly attracting attention and are usually used to manufacture components with complex structures in practical applications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the interlayer has also been shown by MacDonald and Eagar4 to be equally as important as the interlayer thickness. In the published literature, it has been shown that pure metal interlayer such as nickel, 5 5,6 silver 7 7,8 and copper 8 8,9 can react with the metal surface by means of eutectic or peritectic reaction to displace surface oxides. In joints made using these pure interlayers, the existing problems can be summarised as parent metal dissolution particulate segregation,8 – 10 void formation in particle segregated region7 and low strength microbonds at particle/metal interfaces resulting from the poor wettability of molten interlayer on ceramic reinforcement 7 …”
Section: Introductionmentioning
confidence: 99%